Analyzing the role of resource factors in citizens' intention to pay for and participate in disaster management - Kim, Seoyong; Kwon, Seol A.; Lee, Jae Eun; Ahn, Byeong Cheol; Lee, Ju Ho; An, Chen; Kitagawa, Keiko; Kim, Dohyeong; Wang, Jaesun (Sustainability (Switzerland), 2020)
This study aimed to analyze how resource variables (health status, economic affordability, social network, social capital, and neighborhood environment) influence citizens' intention to pay for and participate in disaster management and safety activities. We compared four psychometric paradigm variables with five resource variables and analyzed how the latter moderate the relationships of the perception variables with intention to pay and to participate. A regression analysis revealed that willingness to pay was mainly explained by trust, followed by social capital, economic affordability, perceived risk, and experience, respectively. Participation was explained by knowledge, social capital, age, trust, and social network, respectively. Gender, trust, and social capital had an influence both on willingness to pay and to participate. Perceived risk, knowledge, and trust had a moderating effect on willingness to pay, but this effect depended on the quality of the neighborhood environment. Trust, knowledge, and stigma had a moderating effect on participation intention, but this effect depended on social capital and the neighborhood environment.
Keywords: Disaster management; Intention to participate; Psychometric paradigm; Resource factors; Risk and crisis management; Willingness to pay